Preoperative platelet distribution width‐to‐platelet ratio combined with serum thyroglobulin may be objective and popularizable indicators in predicting papillary thyroid carcinoma - Jin, Jin; Wu, Guihua; Ruan, Chengwei; Ling, Hongwei; Zheng, Xueman; Ying, Changjiang; Zhang, Ying (Journal of clinical laboratory analysis, 2022)
Objectives The incidence of papillary thyroid carcinoma (PTC) has increased more rapidly than that of any other cancer type in China. Early indicators with high sensitivity and specificity during diagnosis are required. To date, there has been a paucity of studies investigating the relationship between preoperative platelet distribution width‐to‐platelet count ratio (PPR) and PTC. This study thus aimed to assess the diagnostic value of PPR combined with serum thyroglobulin (Tg) in patients with PTC. Methods A total of 1001 participants were included in our study. 876 patients who underwent surgery for nodular goiter were divided into the PTC group or benign thyroid nodule (BTN) group according to pathology reports, and 125 healthy controls (HCs) were included. Preoperative hemogram parameters and serum Tg levels were compared among three groups. Receiver operating characteristic (ROC) curve was used to evaluate the value of PPR combined with serum Tg for diagnosing PTC. Results Platelet distribution width (PDW) and PPR levels were higher in the PTC group than in the BTN and HC groups (both p < 0.05) but did not significantly differ between the BTN and HC groups. PDW and PPR levels significantly differed in the presence/absence of lymph node metastasis, the presence/absence of capsule invasion (p = 0.005), and TNM stages (p < 0.001). Multivariable analyses indicated that high serum Tg levels [adjusted odds ratio (OR), 1.007; 95% confidence interval (CI), 1.004–1.009; p < 0.001], high neutrophil‐to‐lymphocyte ratio (NLR,adjusted OR, 1.928; 95% CI, 1.619–2.295; p < 0.001), and high PPR (adjusted OR, 1.378; 95% CI, 1.268–1.497; p < 0.001) were independent risk factors for PTC. In ROC analysis, the areas under the curves (AUCs) of serum Tg, PDW, PPR, and NLR for predicting PTC were 0.603, 0.610, 0.706, and 0.685, respectively. PPR combined with serum Tg (PPR + Tg) had a higher diagnostic value (AUC, 0.738; sensitivity, 60%; specificity, 74.7%) compared with PDW + Tg (AUC, 0.656; sensitivity, 64.4%; specificity, 59.9%) and NLR + Tg (AUC, 0.714; sensitivity, 61.6%; specificity, 71.1%). Conclusions Preoperative PPR combined with serum Tg may be objective and popularizable indicators for effective predicting PTC. Platelets play essential roles in tumorigenesis and progression, however, they are subtle in PTC. Monitoring platelet distribution volume‐to‐platelet ratio combined with thyroglobulin changes can predict PTC occurance.